Local Wisdom and Islamic Educational Values: A Study on the Formation of Rahmatan lil ‘Alamin Student Profile in Southeast Sulawesi - Dewi, Juliana Sinta (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
This study examines the relationship between local wisdom and Islamic education values in shaping the character profile of Rahmatan lil ‘Alamin students in Southeast Sulawesi. The main issue addressed is how the integration of local wisdom can enrich Islamic education and foster the development of students with noble character. The study aims to explore the impact of local wisdom on shaping student profiles within the context of Islamic education and analyze its effects on both theory and practice. A qualitative approach was employed, utilizing in-depth interviews, participatory observation, and document analysis in several schools in Southeast Sulawesi. The findings reveal that local wisdom plays a significant role in strengthening Islamic education values such as compassion, justice, and social responsibility, which are reflected in students' behavior. The integration of local wisdom into Islamic education contributes to the development of students who are not only academically competent but also socially and morally mature. Its impact on Islamic education theory enriches the contextual approach to character education. The practical implication is the need to adapt the curriculum to integrate local wisdom to shape more holistic students. This study offers recommendations for developing education policies that are based on local wisdom and religious values.